The strategic protein. Global dependence and regional changes in the production and use of soy protein for animal feed. (Desarrollo, Estado y Espacio, 2025)
This paper aims to estimate and briefly describe the evolution of the production and use of plant protein, particularly soy protein, for animal feed, and to characterize different regions of the world according to their degree of dependence on imported protein. The paper evaluates the evolution of these regional dependencies on a global scale (considering the United Nations geo-schema) over a set of key years that allow for a description of their trajectory: 1961 (the first statistical data available), 1979, 2001, 2013, and 2022. The goal is to acquire a more precise understanding of the external dependence of different regions on soy protein for animal feed and to observe the main changes in this area. The paper concludes by observing a geographical structure of relative positions around which common interests and dependency relationships arise, which can help to understand behaviors in the arena of international relations.
Keywords: soy; meat; geopolitics; regions; depende